Assessment Of Quality Of Life, Economic And Clinical Outcomes Among Patients With Schizophrenia In Universiti Kebangsaan Malaysia Medical Centre - Taha, Nur Akmar (2011)
Schizophrenia is a chronic and serious mental illness that occurs early and persists for a lifetime. It has significant personal, social & economic impact on the patients, families and society. The objective of the study was to determine and compare the impact of different types of antipsychotic maintenance treatment on humanistic, economic and clinical outcomes in routine clinical practice. The study was prospective and observational in nature. Patients were grouped into two treatment groups; atypical and typical treatment group and assessed at baseline, 3, 6 and 12 months. Health-related quality of life (HRQoL) outcomes were assessed by disease specific scale, the Schizophrenia Quality of Life Scale Revision 4 (SQLS-R4) and generic scale, the EuroQoL Group EQ-5D.